Copy trading [dataset] - Apesteguia, Jose; Oechssler, Joerg; Weidenholzer, Simon (Universität, 2020)
Copy trading allows traders in social networks to receive information on the success of other agents in financial markets and to directly copy thei...
Gesehen am 04.01.2020
Keywords: Forschungsdaten; Datenbank